(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The primary objective of this study is to evaluate the service quality of Samgyeopsal sa Batasan, a restaurant located in Quezon City. Service quality is a multi-dimensional concept that reflects customers’ overall evaluation of the superiority or inferiority of a service. It refers to the extent to which a service meets or exceeds customers’ expectations in terms of various attributes such as reliability, responsiveness, assurance, empathy, and tangibles. An accurate and comprehensive assessment of service quality is essential for service providers to develop effective strategies for improving service quality and enhancing customer satisfaction. The study utilized a survey questionnaire via Google Forms to assess the service quality of Samgyeopsal Sa Batasan. The results of this study indicated that the assessment of service quality at Samgyeopsal Sa Batasan yielded a total average mean of 3.37 for reliability, 3.37 for responsiveness, 3.43 for assurance, 3.43 for empathy, and 3.25 for tangibles. These scores were interpreted as "Agree" suggesting that customers generally agreed that the restaurant met their expectations in these dimensions of service quality. For challenges encountered in Samgyeopsal sa Batasan, slow service is the highest rating with 27 respondents, equivalent to 54%; unavailability of certain products or services and problems with the equipment and overall atmosphere got 13 responses, equivalent to 26% and both got the 2nd rank. Next, none or no challenges encountered got 11 responses, equivalent to 22%, and got the 3rd rank. The recommendations that the researchers will take to Samgyeopsal sa Batasan are to have fast and friendly communication and achieve all customer expectations in terms of food quality and food service. Consider factors such as space, layout, and customer flow to avoid compromising existing customers’ comfort and experience. Ensure that the addition of new seating does not compromise the overall design and functionality of the restaurant.